Medicinal Plant Lexemes Geography and Name in Chiang rai Province - Mavong, Piyamas; Chaimano, Kanita; Chaimano, Boonlue; Krutmueang, Sanom (Academic MCU Buriram Journal, 2023)
The purposes of this research were: 1) to analyze the names of medicinal plants lexemes, 2) to study this lexical variations in naming medicinal plants, and 3) to create mapping the geography of medicinal plants lexemes in Chiang Rai Province. This study consists of information and area scope by a term for herbs, plant types, and 18 districts in Chiang Rai province. The research result found that: 1. The lexemes used in naming medicinal plants in Chiang Rai Province consisted of 4 main parts including plant terms, plant names markers, stems, and plant name extension, which each district has the same name. In particular, when compared to standard Thai, it was found that 5 districts are Muang, Mae Lao, Wiang Chai, Mae Chan and Chiang Saen District have the most different uses of herbaceous plants. 2. Lexical variation for herbaceous plants found in both monosyllabic words and polysyllabic words such as syllable variation of the name or extension is the core of name, extension with more than one syllable or two syllables. The name has two syllables different from the standard Thai language. But two syllables in the northern Thai language, the word variant are two syllables or several syllables. The name of most herb plants is found as a noun with a language structure, including Khammul (Basic words that have meanings that are complete on their own), Kaenchue (lexical items), adverb, adverb of color, compound words. Currently, all variations are found in other widely used meanings. 3. Geographical language map, vocabulary of medicinal plants in Chiang Rai province. Province found the distribution of herbal plant terminology 18 districts because they have different words and different origins, which are called according to the visual characteristics. It is called according to the language of the tribe, called by the original roots, called by the boundaries of ethnic groups, called by the characteristics of sound erosion, and called by the characteristics of habitats.